Local Leadership in a Global Era Policy and Behaviour Change in Cities - Hochadel, Amy M. (Springer International Publishing, 2018)
This book examines local leadership and policy changes as a result of globalisation. The author identifies what behaviours are facilitating the connection of local economies to the global economy and what local structures enable or inhibit the activity. It presents positive indicators from empirical research and three local case studies, that a dyadic arrangement of transformational leadership and a legislative-activist structure are more likely to connect a local economy to opportunities in the global economy. Further, the research presents a new measure for behaviour and structure to deduce the potential for local participation in a global economy. The book is based in and expands several fields of study, and will appeal to scholars of international relations, economics, public management, immigration and politics.